2016
DOI: 10.15586/jcbmr.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Is Aristolochic Acid Really the Cause of the Balkan Endemic Nephropathy?

Abstract: In recent years, aristolochic acid has been promoted vigorously as the causal agent of the Balkan endemic nephropathy because of similarities to some other nephropathies, association with DNA adducts and a perception of human exposure via bread. Critical evaluation of the literature exposes flaws in these aspects, and there has been consistent failure of experimental toxicology to mimic either the slow silent bilateral atrophy of the Balkan disease or the transitional cell carcinomas in the upper urothelium. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Although environmental exposure to AAs has long been claimed to be the trigger for the mechanisms of BEN, specifically, in the hypothesis that the fruit of A. clematitis comingles with wheat grains during the harvesting process, no scientific evidence has been provided to support this claim [15]. Questions have been raised as to this proposal because of the different ripening times of wheat and A. clematitis in the Balkans (Figure 3); while wheat is ripe in early summer (end of June-beginning of July), the fruit of A. clematitis, which is rich in AAs, matures in late July [20,21]. Moreover, the significantly different sizes and weights between an A. clematitis fruit and wheat would result in most of the coharvested A. clematitis seeds being discarded during the threshing and milling processes [21].…”
Section: The Occurrence Of Aristolochic Acids In the Environmentmentioning
confidence: 99%
“…Although environmental exposure to AAs has long been claimed to be the trigger for the mechanisms of BEN, specifically, in the hypothesis that the fruit of A. clematitis comingles with wheat grains during the harvesting process, no scientific evidence has been provided to support this claim [15]. Questions have been raised as to this proposal because of the different ripening times of wheat and A. clematitis in the Balkans (Figure 3); while wheat is ripe in early summer (end of June-beginning of July), the fruit of A. clematitis, which is rich in AAs, matures in late July [20,21]. Moreover, the significantly different sizes and weights between an A. clematitis fruit and wheat would result in most of the coharvested A. clematitis seeds being discarded during the threshing and milling processes [21].…”
Section: The Occurrence Of Aristolochic Acids In the Environmentmentioning
confidence: 99%
“…Later, investigations revealed that it was due to the conflation of similar names (Han Fang Ji and Guang Fang Ji) of two herbs ( Stephania tetrandra and Aristolochia fangchi ) in Chinese and due to erroneous botanical classification 29 . AA is implicated as a cause of Balkan‐endemic nephropathy (BEN), which is endemic in Serbia, Bosnia, Croatia, Bulgaria and Romania, where Aristolochia clematitis is widely present, 30,31 although there is some controversy 32–34 . What is noncontroversial, however, is that AA can cause a rapidly progressive kidney disease often associated with a high incidence of upper urothelial cancer and is responsible for many cases through either use as herbal medicine or food contaminant throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…29 AA is implicated as a cause of Balkan-endemic nephropathy (BEN), which is endemic in Serbia, Bosnia, Croatia, Bulgaria and Romania, where Aristolochia clematitis is widely present, 30,31 although there is some controversy. [32][33][34] What is noncontroversial, however, is that AA can cause a rapidly progressive kidney disease often associated with a high incidence of upper and plants containing AA are still available via the Internet. 31,35 Previous studies investigating the mechanisms of AAN suggested that AAI acts mainly on proximal renal tubular epithelial cells 36,37 activating MAPK/extracellular signal-regulated kinase 1/2 (MEK/ERK1/2) signalling pathway, followed by depletion of intracellular GSH, 38 NQO1, CYP1A1/2, reduced organic anion transporters (OAT), inhibition of PI3K-Akt signalling, and activation of NF-κB, mitophagy, Rap1 signalling and TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent risk factor for BEN is dietary exposure to aristolochic acid (AA) in bread from seeds of Aristolochia clematitis comingling with wheat grain [42, 43]. However, this dietary route of exposure remains questionable given the lack of temporality between the presence of ripe A. clematitis seeds and when wheat is harvested [44, 45] as well as the amount and time of exposure to dietary AA needed to develop BEN (i.e., eating bread daily with at least seven mature seeds of A. clematitis for the past seven decades) [45, 46]. Unfortunately, the role of AA in the etiology of BEN was not pursued by the scientific community until the early 1990s when a high incidence of rapidly progressive tubulointerstitial renal disease was reported among a group of Belgian women who were taking herbal dietary supplements that accidentally contained Aristolochia fangchi , an Aristolochia species [47].…”
Section: Discussionmentioning
confidence: 99%